2016
DOI: 10.1371/journal.pone.0162860
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Value of Primary Synthetic Wheat Genotypes for Grain Yield

Abstract: To introduce new genetic diversity into the bread wheat gene pool from its progenitor, Aegilops tauschii (Coss.) Schmalh, 33 primary synthetic hexaploid wheat genotypes (SYN) were crossed to 20 spring bread wheat (BW) cultivars at the International Wheat and Maize Improvement Center. Modified single seed descent was used to develop 97 populations with 50 individuals per population using first back-cross, biparental, and three-way crosses. Individuals from each cross were selected for short stature, early headi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 47 publications
2
40
0
Order By: Relevance
“…In the context of selecting new parental lines based on GEBV alone, it was recently observed that selecting for high FHB resistance in winter wheat was not that reliable, as only 19% of the lines (9 out of 47) correctly predicted by GEBV belong to the best 10% for FHB resistance [35]. In another study, negative GEBV for yield were observed for synthetic hexaploid spring bread wheat lines evaluated across heat and irrigated environments [36]. Selection for drought tolerance in maize using GEBV, in contrast, has resulted in rapid genetic gains and positive selection responses through using molecular markers associated with yield under drought stress [37].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of selecting new parental lines based on GEBV alone, it was recently observed that selecting for high FHB resistance in winter wheat was not that reliable, as only 19% of the lines (9 out of 47) correctly predicted by GEBV belong to the best 10% for FHB resistance [35]. In another study, negative GEBV for yield were observed for synthetic hexaploid spring bread wheat lines evaluated across heat and irrigated environments [36]. Selection for drought tolerance in maize using GEBV, in contrast, has resulted in rapid genetic gains and positive selection responses through using molecular markers associated with yield under drought stress [37].…”
Section: Discussionmentioning
confidence: 99%
“…tauschii) to improve modern wheat; i.e. grain yield (Jafarzadeh et al 2016). These advanced breeding strategies, coupled with the benefit derived from the wheat genomics era (Uauy 2017), are essential requirements for ensuring a rapid return to the applied wheat research programs, which cannot do without the deep characterization of the functional intergenic space of the genome.…”
Section: Discussionmentioning
confidence: 99%
“…In wheat, new polyploids made by crossing different goatgrass variants with tetraploid wheats have captured a wide range of useful genetic variation. These 'synthetic' wheats are crossed into elite wheat lines and then backcrossed to fix desired phenotypes 64 . A durum wheat (pasta wheat; Triticum durum) line that maintains high yields when grown in saline soil was created by introgressing a region of the einkorn wheat (T. monococcum) genome (a diploid progenitor of tetraploid durum wheat and hexaploid bread wheat) that contains a sodium exclusion pump 65 .…”
Section: Accessing Genetic Diversitymentioning
confidence: 99%